2006
DOI: 10.1016/j.ejpoleco.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Jack Hirshleifer: A Nobel Prize left unbestowed

Abstract: Jack Hirshleifer contributed to investment theory, information economics, conflict, and bioeconomics, clarified the foundations of investment and capital theory in the spirit of Fisher, and made basic contributions to the analysis of covariance risk, gambling and insurance, the Modigliani-Miller Theorem, and public investment through a focus on time, uncertainty and information. He formulated new models of public goods, added to understanding of contest success functions, and explained the paradox of power. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Hirshleifer was an economist who showed that the logic of economic evolution (in effect, classical physical dynamics, as used in the computations of the Section 3 predictions) could allow biology to favor "sacrificial" individuals-"altruistic evolution" was thus found to be favored by ordinary classical mechanics devices. Indeed, much of our current understanding of how Darwinian theory explains human culture and how human creativity using mental processes causes social evolution, are fundamentally due to Hirshleifer [99]; see also [100].…”
Section: Forecasting Evolutionmentioning
confidence: 99%
“…Hirshleifer was an economist who showed that the logic of economic evolution (in effect, classical physical dynamics, as used in the computations of the Section 3 predictions) could allow biology to favor "sacrificial" individuals-"altruistic evolution" was thus found to be favored by ordinary classical mechanics devices. Indeed, much of our current understanding of how Darwinian theory explains human culture and how human creativity using mental processes causes social evolution, are fundamentally due to Hirshleifer [99]; see also [100].…”
Section: Forecasting Evolutionmentioning
confidence: 99%
“…As previously mentioned, Hirshleifer (1991) introduced the notion of the POP, while Skaperdas (1992) and Skaperdas and Syropoulos (1997) further developed and refined his analysis. Discussing the empirical relevance of the POP, Hirshleifer (1991) assigns a fundamental role to the effectiveness of conflict (see also Hausken 2005). However, to the best of our knowledge, none of these works consider the possibility that the POP operates at different levels, simultaneously holding within groups and failing for conflict across groups.…”
Section: Related Literaturementioning
confidence: 99%
“…These theoretical predictions are in line with several well-known empirical regularities on international conflict. For example, Haas (1965) and Zinnes (1972) document that developed countries are more prone to engage in foreign conflicts than developing countries. Hazlewood (1973) and Kegley et al (1978) show that countries' internal turmoil correlates negatively with external conflict engagement.…”
Section: Corollarymentioning
confidence: 99%